2011
DOI: 10.1108/01140581111185490
|View full text |Cite
|
Sign up to set email alerts
|

The impact of New Zealand's disclosure reform on differential managerial disclosure behaviour for good news versus bad news firms

Abstract: PurposeThe purpose of this paper is to investigate the impact of the introduction of New Zealand's statutory‐backed continuous disclosure regime enacted in December 2002 on the differential disclosure behaviour of New Zealand firms with good and bad earnings news.Design/methodology/approachThis paper examines the level of information disclosure, analyst forecast error and forecast dispersion, abnormal returns and abnormal volumes for firms with good and bad news earnings announcements in a sample period surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…These comments appear to imply that stakeholders' attitudes and responses to the type of information released can shape voluntary disclosure practices by familycontrolled companies. This finding is consistent with that of Marsden et al (2011), who argue that stakeholders' reactions, particularly those of investors, play an important role in the amount and type of information disclosed (see also Mistry et al 2014). This shows that external factors, such as stakeholders and the business environment, influence the extent to which companies disclose information.…”
Section: Although It [Voluntary Disclosure] Creates An Opportunity Fo...supporting
confidence: 89%
“…These comments appear to imply that stakeholders' attitudes and responses to the type of information released can shape voluntary disclosure practices by familycontrolled companies. This finding is consistent with that of Marsden et al (2011), who argue that stakeholders' reactions, particularly those of investors, play an important role in the amount and type of information disclosed (see also Mistry et al 2014). This shows that external factors, such as stakeholders and the business environment, influence the extent to which companies disclose information.…”
Section: Although It [Voluntary Disclosure] Creates An Opportunity Fo...supporting
confidence: 89%
“…Skinner (1994) and Cotter et al (2011) found that managers disclose negative information to avoid stakeholder litigation, reputation costs for failure to disclose and to maintain the firms’ equity value. Alternatively, managers may choose to disclose more positive information, to signal “good news” to the market (Linsley and Shrives, 2006; Zhang et al , 2013), their effectiveness in identifying, measuring and managing risk (Elshandidy et al , 2013) and to reduce the possibility of stock undervaluation (Weisbach, 1988; Marsden et al , 2011). Therefore, both “positive” and “negative” disclosures would indicate a higher quality of RMD than “no-direction”.…”
Section: Risk Management Disclosures Frameworkmentioning
confidence: 99%
“…Song and Tuoriniemi (2015) demonstrate that banks provide more favorable loan contracting terms to firms with superior accounting quality. Marsden et al, (2011) show that New Zealand's disclosure reform has reduced information asymmetry problems. Russell (2015) presents evidence that continuous firm disclosure positively affects stock price adjustment to information.…”
Section: Hypothesismentioning
confidence: 98%